Preparation of gelatin/Fe3O4 composite scaffolds for enhanced and repeatable cancer cell ablation. Issue 34 (3rd August 2016) - Zhang, Jing; Li, Jingchao; Chen, Shangwu; Kawazoe, Naoki; Chen, Guoping
Abstract : Gelatin/Fe3 O4 composite scaffolds with controlled pore structures were prepared by a facile ice particulate templating method and they showed great potential for near-infrared photothermal cancer therapy. Abstract : Various nanomaterials have been extensively investigated for photothermal ablation of cancer cells because of their high photothermal conversion efficiency. However, the poor targeting specificity and low repeated heating efficiency of nanomaterials restrict their applications in the clinic. In this work, porous gelatin/iron oxide (Gel/Fe3 O4 ) composite scaffolds were prepared by a facile ice particulate templating method for efficient and repeatable cancer cell ablation. Gel/Fe3 O4 composite scaffolds showed controlled porous structure consisting of large pores and interconnecting small pores. The strong absorption in the near-infrared (NIR) region enabled the Gel/Fe3 O4 composite scaffolds to elevate local temperature quickly under NIR laser irradiation. The composite scaffolds allowed cell adhesion and proliferation showing good biocompatibility. Cancer cells entrapped in the scaffolds could be efficiently killed during laser irradiation. Moreover, the therapeutic efficacy of Gel/Fe3 O4 composite scaffolds could be enhanced by repeated laser irradiation treatment, which is important for clinical application because of the resistant and recurrent nature of cancer. The results indicated that the porous Gel/Fe3 O4 composite scaffolds had good biocompatibility and excellent cancer cell ablation efficacy, which may provide an attractive way to use porous scaffolds for cancer therapy application.